PENERAPAAN GATED RECURRENT UNIT UNTUK PREDIKSI ZAT PENCEMAR UDARA - Jasmine Kezia Halim; Dyah Erny Herwindiati; Janson Hendryli (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Air pollution caused by air pollutant substances is one of the problems of great concern in big cities, including the city of Jakarta. On June 16, 2022, Jakarta has been named the city with the worst source of air pollution in the world. This of course makes the residents of Jakarta and its surroundings feel worried. The purpose of designing this system is to predict air pollutants in DKI Jakarta using the website-based Gated Recurrent Unit (GRU) method. Where the test results from the GRU method produce different predictive values. The MAPE evaluation resulted in good predictions using the GRU method for air pollutants of PM10, SO2, CO, and O3 types with an average MAPE value of less than 50%. However, there are quite bad results for the type of NO2 substance, because it produces a MAPE value of more than 50%. Meanwhile, in the RMSE evaluation, all air pollutants produced an average value of no more than 20% so that it can be said that the GRU method produces predictions that are quite accurate for predicting air pollutants in the DKI Jakarta area.